P142: Gaps in public preparedness to be a substitute decision maker and the acceptability of high school education on resuscitation and end-of-life care: a mixed-methods study. (May 2019) - Wong, M.; Medor, M.; Yelle Labre, K.; Jiang, M.; Frank, J.; Fischer, L.; Cheung, W.
Abstract : Introduction : When a patient is incapable of making medical decisions for themselves, choices are made according to the patient's previously expressed, wishes, values, and beliefs by a substitute decision maker (SDM). While interventions to engage patients in their own advance care planning exist, little is known about public readiness to act as a SDM on behalf of a loved one. This mixed-methods survey aimed to describe attitudes, enablers and barriers to preparedness to act as a SDM, and support for a population-level curriculum on the role of an SDM in end-of-life and resuscitative care.Methods : From November 2017 to June 2018, a mixed-methods street intercept survey was conducted in Ottawa, Canada. Descriptive statistics and logistic regression analysis were used to assess predictors of preparedness to be a SDM and understand support for a high school curriculum. Responses to open-ended questions were analyzed using inductive thematic analysis.Results : The 430 respondents were mostly female (56.5%) with an average age of 33.9. Although 73.0% of respondents felt prepared to be a SDM, 41.0% of those who reported preparedness never had a meaningful conversation with loved ones about their wishes in critical illness. The only predictors of SDM preparedness were the belief that one would be a future SDM (OR 2.36 95% CI 1.34-4.17), and age 50-64 compared to age 16-17 (OR 7.46 95% CI 1.25-44.51). Thematic enablers of preparedness included an understanding of a patient's wishes, the role of the SDM and strong familial relationships. Barriers included cultural norms, family conflict, and a need for time for high stakes decisions. Most respondents (71.9%) believed that 16 year olds should learn about SDMs. They noted age appropriateness, potential developmental and societal benefit, and improved decision making, while cautioning the need for a nuanced approach respectful of different maturity levels, cultures and individual experiences.Conclusion : This study reveals a concerning gap between perceived preparedness and actions taken in preparation to be an SDM for loved ones suffering critical illness. The results also highlight the potential role for high school education to address this gap. Future studies should further explore the themes identified to inform development of resources and curricula for improved health literacy in resuscitation and end-of-life care.